A new fossil genus of net-winged beetles, with a brief review of amber Lycidae (Insecta: Coleoptera) - Kazantsev, Sergey V. (Zootaxa, 2013)
A new fossil genus of net-winged beetles, Protolopheros gen. n., and a new species, Protolopheros hoffeinsorum sp. n., are described from the Baltic amber. The new taxon is placed in Erotini, next to Lopheros Leconte, 1881. The extant Pseudaplatopterus (Eropterus) Green, 1951, comb. n. is lowered in rank and placed as a subgenus of the fossil Pseudaplatopterus Kleine, 1940. The extant Kolibaceum (Laterialis) Kazantsev, 1990, comb. n. is lowered in rank and placed as a subgenus of the fossil Kolibaceum Winkler, 1987.